292. ROLE OF PREOPERATIVE NEOADJUVANT CHEMORADIOTHERAPY FOR LOCALLY ADVANCED BORDERLINE RESECTABLE THORACIC ESOPHAGEAL CANCER. (24th September 2022) - Wakita, Akiyuki; Motoyama, Satoru; Sato, Yusuke; Fujita, Hiromu; Kemuriyama, Kohei; Hayashi, Kenjiro; Minamiya, Yoshihiro
Abstract: The results of the JCOG1109 trial indicate that the standard preoperative neoadjuvant therapy is Docetaxel-cisplatin-fluorouracil (DCF) combined chemotherapy. However, appropriate preoperative treatment for borderline resectable cases is still controversial. Preoperative CF-RT therapy with more substantial local control continues to be an option for tumors with a high risk of invading adjacent organs. The study participants were 163 cT3 locally advanced thoracic esophageal cancer patients who underwent preoperative CF-RT therapy followed by radical esophagectomy. The patients were partitioned into 58 borderline resectable cases (cT3.5 group) and 105 resectable cases (cT3 group). We compared the clinicopathological features, surgical results, and survival between the two groups to verify the effectiveness of preoperative CF-RT therapy for cT3.5 cases. SCC was the predominant cancer histological type. Significantly more upper and middle mediastinum cases and fewer lower mediastinum cases in the cT3.5 group (p < 0.0001). There were no significant differences in postoperative complications; anastomotic leakage was 12.1%, and recurrent laryngeal nerve palsy was 32.8%. The pCR rate was significantly lower in the cT3.5 group (p = 0.0219). Nineteen patients (32.8%) in the cT3.5 group relapsed. Details of recurrence were locoregional in 7 patients, distant LN in 1 patient, and distant organ in 11 patients. There were no significant differences in neither 5-year OS nor 5-year DFS between the two groups (p = 0.6547, p = 0.8799; respectively). Borderline resectable esophageal cancer (cT3.5) treated with preoperative CF-RT therapy showed a comparable survival rate even though the pCR rate was lower than that of resectable esophageal cancer (cT3). Preoperative CF-RT therapy may still be a promising treatment for locally advanced thoracic esophageal cancer with suspected invasion of adjacent organs.